2015
DOI: 10.1017/s0031182015001158
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofLeishmania Infantumin red foxes (Vulpes vulpes) in Central Greece

Abstract: This is the first record of Leishmania detection in foxes in Greece. Spleen, lymph nodes, bone marrow and blood samples were collected from 47 red foxes (Vulpes vulpes) found dead or captured, narcotized and freed after bleeding, from November 2009 to 2011, in Fthiotida prefecture, central Greece. This is an endemic for canine leishmaniasis area with several human visceral leishmaniasis cases. The samples were tested for Leishmania infantum and Leishmania tropica by molecular methods (polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 25 publications
1
32
0
4
Order By: Relevance
“…In addition, it reports the seroprevalence of L. infantum in hares in central and northern Greece for the first time. The occurrence of L. infantum infection in hares, cats, dogs, rodents, red foxes, and humans (Diakou et al 2009;Athanasiou et al 2012;Ntais et al 2013;Karayiannis et al 2015;Giannakopoulos et al 2016Giannakopoulos et al , 2017Tsakmakidis et al 2017) is highly suggestive of an overlapping of the sylvatic and the domestic transmission cycles in Thessaly, as has been suggested previously for the region of Thessaloniki, northern Greece (Tsokana et al 2015). This hypothesis is further supported by the exposure of hares to N. caninum and T. gondii, indicating that hares share the same living space with the definitive hosts of these pathogens, namely, wild carnivores such as gray wolves and dogs, and cats or free-ranging felids respectively.…”
Section: Resultssupporting
confidence: 64%
“…In addition, it reports the seroprevalence of L. infantum in hares in central and northern Greece for the first time. The occurrence of L. infantum infection in hares, cats, dogs, rodents, red foxes, and humans (Diakou et al 2009;Athanasiou et al 2012;Ntais et al 2013;Karayiannis et al 2015;Giannakopoulos et al 2016Giannakopoulos et al , 2017Tsakmakidis et al 2017) is highly suggestive of an overlapping of the sylvatic and the domestic transmission cycles in Thessaly, as has been suggested previously for the region of Thessaloniki, northern Greece (Tsokana et al 2015). This hypothesis is further supported by the exposure of hares to N. caninum and T. gondii, indicating that hares share the same living space with the definitive hosts of these pathogens, namely, wild carnivores such as gray wolves and dogs, and cats or free-ranging felids respectively.…”
Section: Resultssupporting
confidence: 64%
“…It has been reported that the domestic dog may be an important reservoir host of L. donovani in eastern Sudan. 22 Some recent studies also reported reservoir hosts for Leishmania parasites other than dogs, such as red foxes in central Greece, 23 cats in the western provinces of Turkey, 24 and Brazilian bats. 25 In India, L. donovani DNA was recently detected in goats.…”
Section: Discussionmentioning
confidence: 99%
“…In domestic animals, a number of studies revealed infection or evidence of infection in cats, equids, sheep and goats . Among wild animals, the red fox has been studied more than others and was found infected in various countries, with prevalence ranging from 0% to 74.6%, depending on the area and the method applied (PCR or serology) . Other carnivores that have been found infected are grey wolves, jackals, European wild cats, polecats, pine martens, stone martens, common genets, Iberian lynxes, Egyptian mongooses, European badgers, weasels and European minks .…”
Section: Introductionmentioning
confidence: 99%